READER-RESPONSE PEDAGOGY AND CHANGES IN STUDENT STANCES IN LITERARY TEXTS - Angeline Ranjethamoney Vijayarajoo; Moses Samuel (The English Teacher, 2013)
Past studies have revealed that readers usually assume an aesthetic stance when responding to literature. Yet students in schools seem to respond in more efferent ways, and this could be attributed to the efferent teaching of literature in schools. An aesthetic stance refers to paying attention to feelings and ideas that words evoke, while the efferent stance refers to reading for information. Both stances are required and valued in reading and response but the preponderance of the efferent stance among students is a concern. Often the joy of reading literature is taken away from students and replaced with efferent informational reading of literary texts. This study examines tertiary students‟ written literary responses before and after reader response activities of two short stories. The responses were categorized according to the efferent/aesthetic continuum by Cox and Many (1992) from levels one to five. The findings revealed that before the exposure to Reader Response, students‟ responses were mostly that of retelling the story with a predominantly efferent stance. After Reader Response was introduced, students still took on a predominantly efferent stance for their responses to the first story, but for the subsequent story, they began to make personal interpretations of the text. Students brought their meanings to the text and not that of the author, teacher or any critic. Implications of the study are related to the importance of reader response in literature teaching, while encouraging and valuing personal interpretation of the students.
Keywords: reader response, efferent stance, aesthetic stance